Enhanced methane fermentation of municipal sewage sludge by microbial electrochemical systems integrated with anaerobic digestion. (15th November 2019) - Vu, Hoai Thi; Min, Booki
Abstract: Sewage sludge from a municipal wastewater treatment plant was fed into a microbial electrochemical system, combined with an anaerobic digester (MES-AD), for enhanced methane production and sludge stabilization. The effect of thermally pretreating the sewage sludge on MES-AD performance was investigated. These results were compared to those obtained from control operations, in which the sludge was not pretreated or MES integration was absent. The soluble chemical oxygen demand (SCOD) in the raw sewage sludge after pretreatment was 31% higher than the SCOD in untreated sludge (5804.85 mg/L vs. 4441.46 mg/mL). The methane yield and proportion of methane in biogas generated by the MES-AD were higher than those of the control systems, regardless of the pretreatment process. The maximum methane yield (0.28 L CH4 /g COD) and methane production (1139 mL) were obtained with the MES inoculated with pretreated sewage sludge. Methane yield and production with this system using pretreated sewage were 47% and 56% higher, respectively, than those of the control (0.19 L CH4 /g COD, 730 mL). Additionally, the maximum SCOD removal (89%) and current generation were obtained with the MES inoculated with a pretreated substrate. These results suggested that sewage sludge could be efficiently stabilized with enhanced methane production by synergistic combination of MES-AD system with pretreatment process. Highlights: Raw sewage sludge was first used as the substrate for methane generation in MES-AD systems. Heat pretreatment of sewage sludge further improved the MES-AD performance. More enhanced methane production was obtained from the MES-AD with heat-treated sludge. The removal of SCOD and VFA in sludge was increased in MES-AD compared to the control.